Cash Waqf Linked Deposit Model's Potential to Support Free Nutritious Meals in Islamic Boarding Schools - Inayah; Muzalifah; Arif Mubarok; Rofi'i (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2025)
This study examines the potential of the Cash Waqf Linked Deposit (CWLD) as a sustainable funding alternative for the Free Nutritious Meal Program (MBG) in Islamic boarding schools, particularly in underdeveloped areas. Using a literature review and content analysis approach, the research analyzes data from various sources, including journals, books, official reports, and news articles, through the lens of Islamic economics and Maqasid al-Sharia. The findings highlight the significant promise of CWLD, given Indonesia’s substantial annual cash waqf potential of 180 trillion Rupiah, despite its currently low realization. CWLD provides a transparent and accountable mechanism for distributing waqf funds and has proven effective in several case studies, particularly within the education sector. However, key implementation challenges remain, such as the absence of specific regulations, low levels of Islamic financial literacy, and the need for greater stakeholder coordination. The study concludes that, with proper management and regulatory support, CWLD could serve as a sustainable funding solution for MBG, thereby improving student welfare and supporting sustainable development in Indonesia. Further research using quantitative data is recommended to measure CWLD’s actual impact more precisely. Penelitian ini menganalisis potensi Cash Waqf Linked Deposit (CWLD) sebagai alternatif pendanaan berkelanjutan untuk Program Makan Bergizi Gratis (MBG) di pondok pesantren, khususnya di daerah tertinggal. Menggunakan metode studi literatur dan analisis konten, penelitian ini menganalisis data dari berbagai sumber seperti jurnal, buku, laporan resmi, dan artikel berita, dengan perspektif ekonomi Islam dan Maqasid al-Sharia. Hasil penelitian menunjukkan adanya potensi besar CWLD, mengingat potensi wakaf uang di Indonesia yang signifikan, yakni 180 Triliun per tahun, meskipun realisasinya masih rendah. CWLD menawarkan mekanisme transparan dan akuntabel untuk menyalurkan dana wakaf, terbukti efektif dalam beberapa studi kasus, terutama di bidang pendidikan. Namun, tantangan implementasi termasuk kurangnya regulasi khusus, rendahnya literasi keuangan syariah, dan perlunya koordinasi antar pemangku kepentingan. Penelitian menyimpulkan bahwa CWLD, dengan pengelolaan yang baik dan dukungan regulasi, berpotensi menjadi solusi pendanaan berkelanjutan untuk MBG, meningkatkan kesejahteraan santri dan pembangunan berkelanjutan di Indonesia. Penelitian lebih lanjut dengan data kuantitatif disarankan untuk mengukur dampak CWLD secara akurat.